2016
DOI: 10.1071/rd15052
|View full text |Cite
|
Sign up to set email alerts
|

miR-424/322 is downregulated in the semen of patients with severe DNA damage and may regulate sperm DNA damage

Abstract: Sperm DNA integrity is an essential factor for accurate transmission of genetic information. Human sperm DNA damage is a common cause of male infertility but the exact mechanism remains poorly understood. Considering the vital role of microRNA (miRNA) in multiple pathophysiological processes, we hypothesised that testicular miRNA is involved in sperm DNA damage during spermatogenesis. Infertile patients with high sperm DNA fragment index (DFI; n=94) were selected from 1090 infertile men and a total of 18 testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…In an infertile knock-out mouse model, increase in unrepaired DNA breaks has been linked with reduced expression of miR-16 and miR-19b in testes [131]. Moreover, analysis of seminal plasmas from 94 infertile men with high sperm DNA fragmentation index has revealed significant downregulation of miR-424 in this group, implicating a role for miR-424 in repair of double-strand breaks during spermatogenesis [111].…”
Section: Seminal Fluidal Mirnas and Male Infertilitymentioning
confidence: 99%
“…In an infertile knock-out mouse model, increase in unrepaired DNA breaks has been linked with reduced expression of miR-16 and miR-19b in testes [131]. Moreover, analysis of seminal plasmas from 94 infertile men with high sperm DNA fragmentation index has revealed significant downregulation of miR-424 in this group, implicating a role for miR-424 in repair of double-strand breaks during spermatogenesis [111].…”
Section: Seminal Fluidal Mirnas and Male Infertilitymentioning
confidence: 99%
“…miR- 322 plays an important role in cell proliferation, cell differentiation, diabetes and male infertility [1820]. The role in inflammatory response is not exactly reported.…”
Section: Resultsmentioning
confidence: 99%
“…miR-322/424 is a member of miR-15/107 family, also known as miR-16 family [16,17]. It is involved in the regulation of cell proliferation, cell differentiation, diabetes and male infertility [15,1820]. In our preliminary study, miR-322 was predicted to target several sites of inflammatory factors using the software programs.…”
Section: Introductionmentioning
confidence: 99%
“…The investigators reported that up-regulated miRNAs presented an enriched localization in introns, affecting relevant genes for spermatogenesis and the predicted targets of the miRNAs contained critical genes associated to infertility [22]. miRNAs can also be a predictor for sperm DNA damage, as demonstrated by Zhao et al (2015), where they showed that miR-424/322 is involved in sperm DNA damage, and that the dysregulation of this miRNA can induce DNA double-strand breaks during spermatogenesis [23].…”
Section: Mirnas As a Biomarker For Male Infertilitymentioning
confidence: 99%
“…Recently, it was demonstrated that dysregulation of miRNAs (miR-29 and miR-424) can induce DNA double-strand breaks during spermatogenesis -further highlighting the increasing role miRNAs have on sperm integrity and function [23].…”
Section: Sperm-specific Mirnas and Male Infertilitymentioning
confidence: 99%